Quantified bodies in the checking loop: Analyzing the choreographies of biomonitoring and generating big data - Parviainen, Jaana (Human Technology, 2016)
Biomonitoring digital devices have become popular in physical activities and are receiving intensive focus as motivational and support vehicles for health. The aim of this article is to develop a new theoretical framework to analyze biomonitoring from the two perspectives constituting the opposite ends of the big data spectrum: individual (micro) and institutional (macro). In applying phenomenology of the body, discussions of choreography, and Latour’s actor–network theory, I seek to evolve a choreography-based approach that can outline feedback systems between embodied practices and the macrolevel choreography of big data. Health informatics data as economic and political assets are illustrated based on netnography. Netnographic methodology pays close attention to online fieldwork and media texts. Emphasizing the lived body in the analysis of knowledge infrastructure, I aim to contribute to the theoretical discussion of human–data interaction. The findings suggest that highly intimate, personal technology can distance people from their lived bodies.